Model‐based treatment optimization of a novel VEGFR inhibitor - Keizer, Ron J.; Gupta, Anubha; Shumaker, Robert; Beijnen, Jos H.; Schellens, Jan H. M.; Huitema, Alwin D. R. (British journal of clinical pharmacology, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Drugs targeting the VEGF‐pathway often show increase in blood pressure (BP) and proteinuria as dose limiting toxicity. However, high dose levels are also considered crucial for anti‐tumour activity. In preclinical models, lenvatinib affects tumour cell proliferation and tumour vascularization, while therapeutic effects were observed in phase I and II trials. WHAT THIS STUDY ADDS • Adverse event guided dose titration, including treatment with anti‐hypertensive treatment and dose de‐escalations can be expected to keep about 80% of patients on treatment with lenvatinib for 16 weeks. Additionally, within subject dose escalation in subjects not experiencing toxicity can considerably increase dose intensity. AIM To evaluate dosing and intervention strategies for the phase II programme of a VEGF receptor inhibitor using PK–PD modelling and simulation, with the aim of maximizing (i) the number of patients on treatment and (ii) the average dose level during treatment. METHODS A previously developed PK–PD model for lenvatinib (E7080) was updated and parameters were re‐estimated (141 patients, once daily and twice daily regimens). Treatment of lenvatinib was simulated for 16 weeks, initiated at 25 mg once daily. Outcome measures included the number of patients on treatment and overall drug exposure. A hypertension intervention design proposed for phase II studies was evaluated, including antihypertensive treatment and dose de‐escalation. Additionally, a within‐patient dose escalation was investigated, titrating up to 50 mg once daily unless unacceptable toxicity occurred. RESULTS Using the proposed antihypertension intervention design, 82% of patients could remain on treatment, and the mean dose administered was 21.5 mg day−1. The adverse event (AE) guided dose titration increased the average dose by 4.6 mg day−1, while only marginally increasing the percentage of patients dropping out due to toxicity (from 18% to 20.8%). CONCLUSIONS The proposed hypertension intervention design is expected to be effective in maintaining patients on treatment with lenvatinib. The AE‐guided dose titration with blood pressure as a biomarker yielded a higher overall dose level, without relevant increases in toxicity. Since increased exposure to lenvatinib seems correlated with increased treatment efficacy, the adaptive treatment design may thus be a valid approach to improve treatment outcome.